(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to examine the effect of mandatory disclosure and Good Corporate Governance (GCG) on audit quality in companies listed in the LQ-45 indeks on the Indonesia Stock Exchange during the period 2022-2024. The research employs binary logistic regression analysis with a sample of 78 companies that are consistently listed with complete finansial reports. The results indicate that GCG has a positive and significant impact on audit quality, reflected by an increased lokelihood of companies being audited by Big Four Public Accounting Firms, which are known for higher audit quality. In contrast, mandatory disclosure does not have a significant effect on audit quality. These findings emphasize the importance of GCG practices in improving audit quality, as good governance can reduce conflicts between shareholders and management. Therefore, this study recommends strengthening the GCG framework to enhance audit quality and suggests that regulatory focus should be directed toward improving corporate governance).